Does Culture Matter in Economic Behavior? Ultimatum Game Bargaining Among the Machiguenga of the Peruvian Amazon - Henrich, Joseph (American Economic Review, 2000)
Does Culture Matter in Economic Behavior? Ultimatum Game Bargaining among the Machiguenga of the Peruvian Amazon by Joseph Henrich. Published in volume 90, issue 4, pages 973-979 of American Economic Review, September 2000